Care and support needs of injecting drug users attending in Naulo Ghumti, Nepal, Pokhara. - Koirala,Iechha (2009)
ABSTRACT: The study conducted was entitled 'Care and Support Needs of Injecting Drug Users Attending in Naulo Ghumti Nepal, Pokhara' with overall objective to find out the care and support needs of injecting drug users. The study was conducted among 100 injecting drug users by applying cross sectional descriptive research design. Non-probability purposive sampling technique and technique of interview was used to collect data. The finding of the study reveled that majority (91.00%) had heard about care and support services for injecting drug users (IDUs). Among therm majority 84 (32.43%) have knowledge about needle and syringe exchange services. Among all the disclosed respondents got family support. The respondents 28 (50.90%) were taking services irregularly due to inaccessibility. Most (51.00%) of the respondents reported that they were suffering from illness or problems after taking drugs. Among them most (67.41%) mentioned bacterial and viral infections (abscess, STIs, tuberculosis), (4.49%) HIV infection, (4.24%) depression. These all data suggested that needed primary preventions (outreach, information and education, etc), secondary interventions (medical care including plan of treatment, commonly care of abscesses) linkage to drug treatment services as well as interventions needed to prevent negative health outcomes as well as other services. It was found that IDUs with HIV were co-infected with other infections and social stigma. It was found that psychosocial were greater then medical needs. Majority 47 (23.03) of the respondents demand of needle and syringe exchange and outreach services, counseling and treatment services. The finding of the study suggest that comprehensive care services were needed which meet the medical, drug treatment, psychological and social needs of each IDUs.